2017
DOI: 10.1093/schbul/sbx109
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Volumetric Reductions in Schizophrenia and Schizoaffective Patients Displaying Compromised Cognitive Abilities

Abstract: This pattern of more prominent brain structural abnormalities in the group with the most marked cognitive impairments-both currently and putatively prior to illness onset, is consistent with the concept of schizophrenia as a progressive neurodevelopmental disorder. In this group, neurodevelopmental and neurodegenerative factors may be important for cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 43 publications
6
49
0
Order By: Relevance
“…The present results extend this literature, identifying two subgroups that differ in severity of executive dysfunction and a third subgroup exhibiting a relatively intact level of functioning as quantified through the WCST. Historically, schizophrenia spectrum disorder participants have been consistently documented as a single group to exhibit moderately impaired performance on the WCST relative to the HC population (Li, 2004;Van der Does & Van den Bosch, 1992). By applying exploratory cluster analysis, a small proportion of the schizophrenia spectrum participants were identified as having severe impairments on the WCST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results extend this literature, identifying two subgroups that differ in severity of executive dysfunction and a third subgroup exhibiting a relatively intact level of functioning as quantified through the WCST. Historically, schizophrenia spectrum disorder participants have been consistently documented as a single group to exhibit moderately impaired performance on the WCST relative to the HC population (Li, 2004;Van der Does & Van den Bosch, 1992). By applying exploratory cluster analysis, a small proportion of the schizophrenia spectrum participants were identified as having severe impairments on the WCST.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with schizophrenia spectrum disorder (SSD) are commonly reported not to successfully complete the WCST, attributed to an impaired ability to form concepts and engage in flexible thinking (Li, 2004;Polgár et al, 2010;Van der Does & Van den Bosch, 1992;Waford & Lewine, 2010). Previous studies have documented that participants with SSDs require a high number of trials to complete the first category, register a high proportion of perseverative and non-perseverative errors, and frequently break set, resulting in their failure to meet the six categories achieved discontinuation rule before the maximum numbers of trials are administered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, assessment of unaffected biological siblings of such patients (preferably in a discordant twin‐pair design) could help us to ascertain whether their cognition is truly “intact,” based on whether their performance deviates at all from their “genetic cognitive destiny” (see Ref. [] for a discussion of this notion in relation to SZ). A continued focus on testing and refining cognition—enhancing interventions will be important so long as they continue to be informed by growing knowledge of the biological and environmental correlates of cognitive functioning and their covariation over time and illness phases; it is likely that multi‐modal interventions will be among the most efficacious means by which to improve cognitive dysfunction in the illness.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Heterogeneity of premorbid adjustment, illness course, and outcomes is the rule rather than the exception in psychotic disorders, (e.g., [62]), and identifiable subsamples may differ in neuroprogressive degree and trajectory (e.g., [111]). Recent reports suggest that abnormalities in brain structure and connectivity are associated with cognitive subtypes in psychosis [112][113][114]. A recent study found that baseline neurocognitive functioning predicted gray matter reductions in multiple brain regions two years later [115], suggesting that baseline profiles…”
Section: Heterogeneity In Cognition and Neurobiologymentioning
confidence: 99%